Inflasi dan Mobilitas Masyarakat di Masa Pandemi Covid-19 - Yana Hendriana (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2021)
This study aims to analyze the correlation between the inflation rate by expenditure group and the level of community mobility based on the location of visits in West Java during the Covid-19 pandemic. The research method used is the quantitative method through descriptive analysis and correlation analysis. This study uses secondary data from the Central Bureau of Statistics and the Google Mobility Report. The results of this study explain that the total inflation rate has a strong correlation with people's mobility to the central location of the economy. Inflation of primary commodities found in the Food, Beverage, and Tobacco group and the Housing, Electricity, and Fuel group has a weak correlation with the level of community mobility. The results of this study can be used as a basis for policymakers in the context of controlling inflation and capturing phenomena that occur related to restrictions on mobility during the Covid-19 pandemic.